Rekayasa Alat Tanam Bibit Padi (Transplanter) Sederhana Dengan Sistem Crank Untuk Empat Baris Yang Ergonomis, Terjangkau, dan Memotivasi Pemenuhan Kelangkaan Energi Bidang Pertanian - Anang Supriadi Saleh (Jurnal Ilmiah Inovasi, 2017)
One of the activities that absorb a lot of labor is the activity of planting rice seedlings (transplanting seedlings). These activities require about 25% of the labor needs of rice cultivation. the scarcity of labor in agriculture and the declining interest of young people in the agricultural sector is one of the obstacles in the agricultural sector. These constraints can threaten the uniformity of planting time, increase productivity and shrinking rice crops in a stretch or area that will ultimately disturb the achievement of national self-sufficiency rice targets. So the need for an alternative use of mechanization technology for this move planting activity is simple, easy and cheap.The objective of this research is to make transplanter with crankcatching system for two rows which are ergonomic, affordable and suitable for the condition and habits of rice farmers in Indonesia.The design approach for the design of this machine uses a method developed by Gerhardt Pahl and Wolfgang Beitz described in the Engineering Design book, so that the design approach is based on a functional design approach and a structural design approach. Stages of design of this machine include the identification of problems, formulation and refinement of ideas, the selection of design concepts, analysis and drawing work, prototype tool making, testing and refinement prototype tool.The output in this study is a simple planting tool (transplanter) with a crank system for four lines that are ergonomic, affordable, and ready to apply. Plant spacing on the tool is arranged by referring to Government recommendation that is using planting system of legowo, with spacing between line 20 cm, 40 cm, 20 cm, spacing in line 12 cm, while tool width 80 cm. Tests using seedlings that have been seedlings for 20 days, with the average seed height 22 cm.Field testing showed that the rice seedlings plant has a working capacity of 0.16 ha / hour, at a road speed of 2 km / h, the number of seeds per clump of 2 seeds / grove, 5.2 cm planting depth, 90o plant resistance angle, empty 20%, percentage of seeds collapsed 5%, percentage of seeds scattered 5%.Keywords: transplanter, seedlings, rice